An event-triggered round-robin protocol to dynamic output feedback control for nonhomogeneous Markov switching systems. (November 2022) - Cheng, Jun; Park, Ju H.; Yan, Huaicheng; Wu, Zheng-Guang
Abstract: This paper addresses the dynamic output feedback control issue for nonhomogeneous Markov switching systems with an event-triggered round-robin protocol. The transition probability matrix of the nonhomogeneous Markov process is time-varying, which can be characterized by a polytopic structure. To alleviate the communication burden in a shared network, as a first effort, a novel dynamic event-triggered round-robin protocol is forwarded to regulate whether to release the measurements and which ones to release. In light of the dynamic event-triggered round-robin protocol, an asynchronous dynamic output feedback control law is constructed, which reflects the mismatching phenomenon of modes switching between the nonhomogeneous Markov switching systems and the desired controllers. By resorting to a novel Lyapunov functional, sufficient conditions are attained to guarantee the stochastic stability of the augmented dynamic. At last, two examples are addressed to verify the effectiveness and applicability of the theoretic results.